Indonesian Teaching Factory: The Recent Breakthrough in Education at Vocational High Schools - Isnantyo FD; Pardjono Pardjono; Mochamad Bruri Triyono; Asnul Dahar Minghat (Universitas Sebelas Maret, 2024)
Vocational High Schools (VHS) were established to prepare students to work in specific fields. VHS previously used various learning models, but in recent years, they have focused on The Teaching Factory Learning Model. Some VHS that used other learning models previously produced VHS graduate results that did not meet expectations, contributing to a high unemployment rate in Indonesia. This research aims to assess the implementation of The Teaching Factory Learning Model in VHS in Indonesia. It uses a qualitative research approach with a literature study method. The results of this research are: (1) The Teaching Factory Learning Model is the primary choice of learning model implemented by VHS in Indonesia, (2) Vocational Education in Indonesia recognizes three types of TeFa implementation, including (a) VHS providing space for industrial partners, ( b) VHS working with industrial partners to build a shared space outside their location, and (c) VHS conducting learning at the industrial partner's location. The Indonesian government has issued various regulations and revitalized the Teaching Factory to support the successful implementation of this learning model in VHS.